How and why do small firms manage interest rate risk? Evidence from commercial loans - James Vickery (Federal Reserve Bank of New York, 2005)
Although small firms are particularly sensitive to interest rates and other external shocks, empirical work on corporate risk management has focused instead on large public companies. This paper studies fixed-rate and adjustable-rate loans to see how small firms manage their exposure to interest rate risk. Credit-constrained firms are found to match significantly more often with fixed-rate loans, consistent with prior research showing that the supply of internal and external finance shrinks during periods of rising interest rates. Banks originate a higher share of adjustable-rate loans than other lender types, ameliorating maturity mismatch and exposure to the lending channel of monetary policy. Time-series patterns in the share of fixed-rate commercial loans are consistent with recent evidence on debt market timing.
Keywords: G21; G30; 330; fixed-rate loan; adjustable-rate loan; corporate risk management; interest rate risk; Zinsrisiko; KMU; Risikomanagement; Kredit; USA